2019
DOI: 10.1029/2018gl080384
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Mechanical and Hydraulic Properties of Wet and Dry Fault Zones in a Proposed Shale‐Hosted Nuclear Waste Repository

Abstract: The underground disposal of high‐level nuclear waste is a pressing issue for several countries. In Switzerland, the Opalinus Clay formation is a shale with favorable barrier properties. However, small‐to‐large faults intersecting the formation bring the long‐term integrity of the future repositories into question. Here we present the first systematic laboratory study on the frictional strength, stability, dilatancy, and permeability of simulated Opalinus Clay gouge under typical repository conditions. Wet goug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 64 publications
6
30
2
Order By: Relevance
“…The generation of a thin layer fault gouge in the presence of water potentially forming a gel or suspension resembling a highly viscous fluid may partly support normal stress acting between fault walls (Brodsky & Kanamori, 2001). This lubrication process is expected to result in a drop of friction beyond the critical slip distance (Cornelio et al, 2019;Di Toro et al, 2011;Reches & Lockner, 2010), as observed in wet gouges (Orellana et al, 2019;Sammis et al, 2011). Additionally, the real contact area between fault planes is expected to be reduced due to the gradual decrease of effective normal stress during fluid pressurization (Rubinstein et al, 2004).…”
Section: Effect Of Fluid Injection On Frictional Behaviormentioning
confidence: 99%
“…The generation of a thin layer fault gouge in the presence of water potentially forming a gel or suspension resembling a highly viscous fluid may partly support normal stress acting between fault walls (Brodsky & Kanamori, 2001). This lubrication process is expected to result in a drop of friction beyond the critical slip distance (Cornelio et al, 2019;Di Toro et al, 2011;Reches & Lockner, 2010), as observed in wet gouges (Orellana et al, 2019;Sammis et al, 2011). Additionally, the real contact area between fault planes is expected to be reduced due to the gradual decrease of effective normal stress during fluid pressurization (Rubinstein et al, 2004).…”
Section: Effect Of Fluid Injection On Frictional Behaviormentioning
confidence: 99%
“…In this paper, many fault parameters, such as the friction angle, were derived through a calibration procedure because they were not readily available at the time this research was conducted. Recent experimental data for fault properties [7][8][9][10][11][12] will be used in future work. The conditions leading to the generation of seismic events, and estimates of their magnitudes will also be studied.…”
Section: Resultsmentioning
confidence: 99%
“…The shear strength parameters are the key parameters that determine the onset of fault failure, while the damage enhancement parameter determines the magnitude of the permeability increase in the post-failure phase. The friction angle is directly related to the friction coefficient, which has been shown to be highly variable [8,9,12]. Therefore, we performed a sensitivity study in this section, and also consider it spatial variability in the heterogeneous case described in a subsequent section.…”
Section: Effects Of Fault Shear Strength Parametersmentioning
confidence: 99%
See 2 more Smart Citations